Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1995
DOI: 10.1093/jn/125.9.2425
|View full text |Cite
|
Sign up to set email alerts
|

Rat Plasma VLDL Composition and Concentration and Hepatic Lipase and Lipoprotein Lipase Activities Are Impaired during Two Types of Protein Malnutrition and Unaffected by Balanced Refeeding1

Abstract: The relationships between VLDL concentrations and composition and changes in hepatic lipase and lipoprotein lipase activities were determined in rats, during the consumption of two low protein diets (2% casein or 5% gluten) (protein malnutrition) for 28 d, followed by the refeeding of a balanced diet for 14 d (15% casein) (refeeding). A control group was fed 15% casein for 42 d. In the control group, total lipolytic activity increased with age (r = 0.83, P < 0.001), whereas in both depleted groups, this activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…Since decreased VLDL-triglyceride secretion is generally observed in protein-deprived animals, decreased VLDL synthesis and triglyceride transport from the liver, which accompany decreased apolipoprotein B (apoB) levels, have been proposed as the primary mechanism of fatty liver generation. 3,4,[33][34][35] In accord with these observations, we found significant decreases in plasma triglyceride concentrations in the 5C animals, and this occurred independently of insulin administration. Furthermore, although its role in protein malnutrition remains largely unknown, endoplasmic reticulum stress, which promotes steatosis, has recently been found to inhibit apoB secretion.…”
Section: Insulin Injection During Protein Restriction 135supporting
confidence: 87%
“…Since decreased VLDL-triglyceride secretion is generally observed in protein-deprived animals, decreased VLDL synthesis and triglyceride transport from the liver, which accompany decreased apolipoprotein B (apoB) levels, have been proposed as the primary mechanism of fatty liver generation. 3,4,[33][34][35] In accord with these observations, we found significant decreases in plasma triglyceride concentrations in the 5C animals, and this occurred independently of insulin administration. Furthermore, although its role in protein malnutrition remains largely unknown, endoplasmic reticulum stress, which promotes steatosis, has recently been found to inhibit apoB secretion.…”
Section: Insulin Injection During Protein Restriction 135supporting
confidence: 87%
“…Moreover, in protein-depleted rats, Agbedana (1980) showed that LPL activity is significantly reduced in adipose tissue, whereas there are no significant changes in heart and liver lipolytic activities. In a previous study, we have shown that total plasma lipolytic activity, which represents HL and LPL activities, remains low and stable in rats throughout the period of protein malnutrition (Lamri et al 1995). We have also observed that VLDL composition varies significantly with the type of protein malnutrition (50 g wheat gluten or 20 g casein/kg).…”
mentioning
confidence: 66%
“…In addition to modulating energy intake and expenditure, moderate protein restriction in rats and mice has been consistently associated with alterations in body composition including reduction in lean mass, increased body fat content and development of fatty liver 6 8 9 14 17 32 33 . Protein restricted rats attempt to catch-up on body weight and adipose reserves following refeeding on a standard protein diet 34 35 36 37 38 . However, less is known of the temporal changes in body composition, energy intake and energy expenditure following realimentation of protein restricted animals to standard protein diets.…”
mentioning
confidence: 99%